Case Study Of ST Microelectronics N.V. - Ong, Melanie Ling Ling (2008)
ST Microelectronics N.V. is a multinational company that designs, develops,manufacturers and markets a broad range of products used in a wide variety of microelectronics applications, inluding telecommunications systems, computer systems,consumer goods, automotive products and industrial automation and control system.